2020
DOI: 10.1038/s41421-020-0168-9
|View full text |Cite|
|
Sign up to set email alerts
|

Immune cell profiling of COVID-19 patients in the recovery stage by single-cell sequencing

Abstract: COVID-19, caused by SARS-CoV-2, has recently affected over 1,200,000 people and killed more than 60,000. The key immune cell subsets change and their states during the course of COVID-19 remain unclear. We sought to comprehensively characterize the transcriptional changes in peripheral blood mononuclear cells during the recovery stage of COVID-19 by single-cell RNA sequencing technique. It was found that T cells decreased remarkably, whereas monocytes increased in patients in the early recovery stage (ERS) of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

54
545
6
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 667 publications
(608 citation statements)
references
References 48 publications
54
545
6
3
Order By: Relevance
“…IL-6 and IP-10 are consistently upregulated during a cytokine storm and are associated with severe ARDS 9,10,31,32 . While some studies report inflammatory monocytes as the source of IL-6 9,33,34 , our results suggest that immature neutrophils could also be a non-negligible source of IL-6 during COVID-19-induced cytokine storm. Indeed, neutrophils have been found to produce biologically relevant amounts of IL-6 after engagement of TLR8, a toll like receptor recognising single strand RNAs of viral or bacterial origin 35,36 .…”
Section: Discussioncontrasting
confidence: 64%
“…IL-6 and IP-10 are consistently upregulated during a cytokine storm and are associated with severe ARDS 9,10,31,32 . While some studies report inflammatory monocytes as the source of IL-6 9,33,34 , our results suggest that immature neutrophils could also be a non-negligible source of IL-6 during COVID-19-induced cytokine storm. Indeed, neutrophils have been found to produce biologically relevant amounts of IL-6 after engagement of TLR8, a toll like receptor recognising single strand RNAs of viral or bacterial origin 35,36 .…”
Section: Discussioncontrasting
confidence: 64%
“…But, NK cells has been prominently reduced in 59% of the cases (higher incidence rate than others) (Wang et al, 2020b). Accumulating evidence had supported the fact that NK cells had reduced in COVID-19 patients as compared with noninfected cases (Chen G. et al, 2020;Wen et al, 2020;Wilk et al, 2020). Of note, a latter study by Feng Wang et al (Wang et al, 2020a) has been reported that CD4+ T cells were increased in patients with COVID-19, whereas the number of NK cells was decreased in the severe stage of infection.…”
Section: Nk Cells-mediated Antiviral Immune Response To Sars-cov2mentioning
confidence: 93%
“…Investigating immune responses to SARS-CoV-2 across all age groups is key to understanding disease susceptibility, severity determinants, and vaccine candidates. Detailed investigations of immune responses during SARS-CoV-2 infection have been reported in adults [10][11][12] , with exposure to SARS-CoV-2 causing speci c T cell responses without seroconversion 13 . Data on immune responses in children exposed to SARS-CoV-2 are limited.…”
Section: Mainmentioning
confidence: 99%